Perancangan Sistem Informasi Akuntansi Penerimaan Dan Pengeluaran Kas Dengan Microsoft Access Pada PT Aldila - Adhyasta Cakra Whisnu Arsyana; Cholis Hidayati; Mochammad Arifin (P3M Politeknik Negeri Bengkalis, 2024)
PT Aldila, a medium-scale construction company, faces challenges in managing cash receipts and expenditures that are still done manually using Microsoft Excel. This process not only slows down work efficiency, but also increases the risk of recording errors that have an impact on the accuracy of financial statements. This condition hinders managerial decision-making that requires fast and accurate financial data. This research aims to design a Microsoft Access-based accounting information system as a solution to improve accuracy and efficiency in managing financial statements. The research method uses qualitative descriptive with a case study approach of system development, collecting primary data through interviews and observations as well as secondary data from company documentation. The research subjects include directors, HRD management, operational management, and accounting staff at two locations of PT ALDILA, with a research duration of three months. Data analysis was carried out to design a Microsoft Access-based accounting information system that supports transparency and accountability of the company's financial reporting. The results of the study show that the implementation of Microsoft Access can minimize errors in recording cash transactions and speed up the reporting process. The designed system is also designed to meet the Financial Accounting Standards (SAK). With the existence of a Microsoft Access-based accounting information system, PT Aldila is expected to be able to increase the company's transparency and accountability, as well as provide convenience in managing cash data. In addition, the results of this research contribute to the development of science in the field of Accounting Information System (SIA) design and provide practical benefits for PT Aldila to support more informative and responsive managerial decision-making to future challenges.